The “Right” History: Religion, Race, and Nostalgic Stories of Christian America - Braunstein, Ruth (Religions (Basel, Switzerland ), 2021)
A wide range of right-wing movements are bound together by their adherence to a nostalgic vision of the United States as a “Christian nation,” yet there are meaningful differences in the specific narratives promoted by these groups that are not fully understood. This article identifies two ideal-typical versions of this narrative: the white Christian nation and the colorblind Judeo-Christian nation. The two narratives share a common declension structure, but differ in their framing of how religion and race intersect as markers of American belonging and power. Although participants in right-wing movements often slide back and forth between the two narratives in practice, distinguishing between them analytically enables us to better understand how the two renderings of American history carry different meanings and perform different kinds of political work for participants in these movements. Theoretically, the analysis extends the insights of a “complex religion” approach to sites beyond organized religion, while also demonstrating how scholarship on Christian nationalism and on right-wing movements’ use of national history could each be enhanced by greater attention to the other.